PERANCANGAN SISTEM INFORMASI LABORATORIUM TEKNIK INDUSTRI UNIVERSITAS NEGERI GORONTALO - Lasalewo, Trifandi; Budjang, Dhimiral Alfasih; Arafat, Muh. Yasser (JURNAL REKAYASA SISTEM INDUSTRI, 2023)
A website is a collection of pages in a domain that contains various information so that it can be read and viewed by internet users through a search engine. This research aims to produce an information system that is used as a management tool for the management of the UNG Industrial Engineering Laboratory. The research method used is the prototype method. This research produces a web-based UNG Industrial Engineering Laboratory information system that makes data storage and laboratory archiving easier and makes it easier for the academic community and the public to obtain information and service needs from the UNG Industrial Engineering Laboratory.